HUBUNGAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS VII PADA MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN MASA PANDEMI COVID DI MTs NEGERI 1 PELALAWAN - Syahfitriani Syahfitriani; Ramadi Ramadi; Hirja Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is a correlation research. This study aims to determine whether there is a relationship between learning motivation and learning outcomes for grade VII students in physical education, sports and health during the COVID-19 pandemic at MTs Negeri 1 Pelalawan. Population 243 students. The sampling technique used a probability sampling technique, namely the simple random sampling technique (15%). The number of samples is 36 students. Collecting data using questionnaires and documentation. Test the validity of the instrument using the product moment correlation with a significant level of 5%. The instrument reliability test using the Cronbach's alpha formula can be seen the value of 0.903 > 0.60. Correlation test shows that the value of rcount for the relationship between learning motivation (X) and learning outcomes of PJOK (Y) is 0.580 > rtable 0.329. Judging from the rcount (Pearson Correlations) which is 0.580 obtained, then the level of relationship between Learning Motivation and Learning Outcomes is stated in the medium category.Key Words: Learning Motivation, Learning Outcomes